Expresión corporal como herramienta para el desarrollo de la coordinación motriz en los niños de Educación Inicial subnivel 2. - Guanoluisa Aquieta, Jenny Patricia (2023)
The present research work with the topic Body Expression as a tool for the development of Motor Coordination in children of Initial Education sublevel 2, had as its main objective to enhance body expression as a tool for the development of Motor Coordination in children of Education Initial sublevel 2 of the “María Montessori” Initial Education Center of the Latacunga Canton, La Matriz Parish, in the 2022-2023 school year, the methodology used had a mixed approach, the type of research will be non-experimental, based on the descriptive – observational since it will allow the data collected to be jointly analyzed through instruments such as the survey and the observation sheet where the data reflected a negative result, with a percentage of 35% being low in the development of the body and motor expression of the children. children of the initial sublevel 2, therefore, the proposal of a brochure of innovative recreational games to strengthen Bodily Expression was proposed, then the innovative activities were applied to the children obtaining positive results, 90%, potentiating the expression body, motor coordination of children in sublevel 2 of Initial Education. It was concluded that the application of activities with recreational games arouses interest and motivation in children of initial education sublevel 2, to achieve optimal development of their motor coordination and body expression.